T1-Mapping in Myocardial Disease Principles and Applications (Springer International Publishing, 2018)
This book details the advances in cardiac MRI that have enabled quantitative tissue characterization of the myocardium using myocardial and blood T1 measurements, which have enabled reliable detection of diffuse pathological processes in both the cardiomyocytes and the interstitial cells of the myocardium. Evaluation of the native myocardial and interstitial fibrosis, and measurement of the extracellular volume fraction has allowed an unprecedented opportunity to elucidate the pathology, diagnosis and prognosis of cardiovascular disease. T1-Mapping in Myocardial Disease: Principles and Applications reviews a wide spectrum of significant cardiovascular disease and provides relevant guidance for the clinical implementation of this innovative technique. The specific topics covered include principles of T1-mapping in cardiovascular disease and the role of T1-mapping in hypertensive heart disease and hypertrophic cardiomyopathy, cardiotoxicity from cancer treatment, cardiacfibrosis, left ventricular hypertrophy in aortic stenosis, peri-infarct injury in ischemic cardiomyopathy, and stem cell therapy. This comprehensive coverage of the utility of T1-mapping in cardiovascular diseases will greatly appeal to the entire cardiovascular medicine and imaging communities. .